Effect of Process Management and Planning and Control on Customer Relations in Assessing Readiness to Deploy Lean Manufacturing Techniques within SMEs: SMART PLS-SEM Approach - Mohammed, Inuwa (INTI International University, 2023)
Most lean initiatives failed because of poor readiness assessments of processes and planning which hinder customer relations. To mitigate such occurrences, the study analyzes the effect of process management, planning and control on customer relations within manufacturing SMEs, aimed to ensure they have the readiness to deploy lean initiatives successfully. The study applied a quantitative survey approach by collecting 300 responses from managers of manufacturing SMEs in Nigeria. The findings of the study show that a positive and significant relationship exists between process management, planning and control on customer relations. It implied that manufacturing SMEs in Nigeria plan and manage their manufacturing processes effectively which leads to enhanced customer relations. Hence, showing a high level of readiness to deploy lean and ensure waste eradication, effective scheduling and improved product quality.